Endothelial function vessel wall measures in patients with gout associated with coronary heart disease - E S Feofanova; L A Knyaseva (Научно-практическая ревматология, 2007)
Objective. To study function of endothelium in pts with gout associated with coronary heart disease (CHD) depending on hyperuricemia (HU) expression. Material and methods. 86 male with primary gout associated with CHD (stable exertional angina pectoris of functional class (FC) II-III) aged 42 to 67 years were included. 30 (34,9%) from them had low, 36 (41,8%) - moderate and 20 (23,3%) - high grade HU. 28 pts with stable exertional angina pectoris of FC II-III were included in the group of comparison and 20 healthy donors - in the control group. Circulating endothelial cells (CEC) quantity was assessed with the method of J. Hladovec (1978), endothelin 1 (ET1) level was evaluated with a radioimmunoassay kit (Amersham, USA), endothelium- dependent vasodilatation (EDVD) was assessed by change of brachial artery (BA) diameter in test with reactive hyperemia. Results. Pts with gout associated with CHD had significantly higher level of CEC and ET1 than pts with CHD. Maximal ET1 level was revealed in gout pts witn CHD and high degree HU (52,2+1,1 ng/1, p,0,01). Uric acid concentration correlated with CEC and ET1 level in serum of gout pts with CHD (r=0,74, p<0,001, r=0,68, p<0,01 respectively). BA EDVD in gout pts with CHD was decreased in comparison with control and pts with CHD. In gout pts with CHD low degree HU associated with maximal (5,2±1,2%) and HU exceeding 620 pmol/l with minimal (2,6±1,1%) relative vasodilatation. Presence of obesity and/or hypertension increased disturbances of endothelium functional state. Conclusion. Combination of gout and CHD was accompanied by increase of CEC, ET1 and decrease of EDVD progressing with increase of HU.